Synthesis and biological activity of furoxan derivatives against Mycobacterium tuberculosis - Fernandes, Guilherme Felipe dos Santos [UNESP]; de Souza, Paula Carolina [UNESP]; Marino, Leonardo Biancolino [UNESP]; Chegaev, Konstantin; Guglielmo, Stefano; Lazzarato, Loretta; Fruttero, Roberta; Chung, Man Chin [UNESP]; Pavan, Fernando Rogério [UNESP]; dos Santos, Jean Leandro [UNESP] (Elsevier, 2016)
Tuberculosis (TB) remains a serious health problem responsible to cause millions of deaths annually. The scenario becomes alarming when it is evaluated that the number of new drugs does not increase proportionally to the emergence of resistance to the current therapy. Furoxan derivatives, known as nitric oxide (NO) donors, have been described to exhibit antitubercular activity. Herein, a novel series of hybrid furoxan derivatives (1,2,5-oxadiazole 2-N-oxide) (compounds 4a-c, 8a-c and 14a-c) were designed, synthesized and evaluated in vitro against Mycobacterium tuberculosis (MTB) H37Rv (ATCC 27294) and a clinical isolate MDR-TB strain. The furoxan derivatives have exhibited MIC90values ranging from 1.03 to 62 μM (H37Rv) and 7.0–50.0 μM (MDR-TB). For the most active compounds (8c, 14a, 14b and 14c) the selectivity index ranged from 3.78 to 52.74 (MRC-5 cells) and 1.25–34.78 (J774A.1 cells). In addition, it was characterized for those compounds logPo/wvalues between 2.1 and 2.9. All compounds were able to release NO at levels ranging from 0.16 to 44.23%. Among the series, the phenylsulfonyl furoxan derivatives (compounds 14a-c) were the best NO-donor with the lowest MIC90values. The most active compound (14c) was also stable at different pHs (5.0 and 7.4). In conclusion, furoxan derivatives were identified as new promising compounds useful to treat tuberculosis.
Keywords: Antituberculosis agents; Furoxan; Mycobacterium tuberculosis; Phenotypic screening; Tuberculosis